Prostate incidentaloma on 18F-fluorodeoxyglucose positron emission tomography: Diagnostic value of volumetric positron emission tomography parameters - Şahin, Özlem; Kaya, Buğra; Aydın, Zeynep; Şen, Ahmet Eren; İyisoy, Mehmet Sinan; Aydın, Arif (Nuklearmedizin - NuclearMedicine, 2021)
Objective To evaluate whether volumetric PET parameters such as metabolic tumor volume (MTV) and total lesion glycolysis (TLG) contributed to maximum standardized uptake value (SUVmax) in predicting prostate carcinoma in the prostate incidentalomas (PI) in 18F-FDG PET/CT.Materials and methods This retrospective study comprised 107 patients with PI of 4723 male patients who had undergone 18F-FDG PET/CT. SUVmax and volumetric PET parameters of PIs were assessed. MTV and TLG were acquired with each SUV threshold as 2.5, 3.0, 3.5, 4.0, 4.5, and 5.0.Results The PI incidence was 2.3%, and the malignancy ratio of PI was 15.9%. According to further analysis results, 17 patients were in the malignant group, and 46 patients were in the benign group. Malignant PIs had higher SUVmax (10.6 vs. 6.4 and p<0.01), MTV (all p < 0.01) and TLG (all p < 0.01) than benign incidentalomas. All volumetric PET parameters had higher area under the curve (AUC) than SUVmax. SUVmax AUC was 0.835 [95% confidence interval (CI): 0.728–0.942]. MTV 2.5 and TLG 2.5 had the highest performance for predicting malignant PI.MTV2.5 AUC was 0.871 (95% CI: 0.775–0.968), and TLG2.5 AUC was 0.882 (95% CI: 0.797–0.967). Using TLG 2.5 greater than 29.8 as the cut-off point, the sensitivity and specificity for malignancy prediction were 94.1% and 82.6%, respectively.Conclusion In this study, in which the effectiveness of volumetric parameters in the diagnosis of PI was evaluated for the first time, it was shown that they could potentially have clinical value along with SUVmax.
Keywords: Prostata-Inzidentalom; volumetrische PET-Parameter; MTV; TLG; SUV